Transgenic modification of the n‐3 HUFA biosynthetic pathway in nibe croaker larvae: improved DPA (docosapentaenoic acid; 22:5n‐3) production. (6th January 2015) - Kabeya, N.; Takeuchi, Y.; Yazawa, R.; Haga, Y.; Satoh, S.; Yoshizaki, G.
Abstract: Marine fish are generally unable to produce sufficient quantities of n‐3 highly unsaturated fatty acid (n‐3 HUFA) such as eicosapentaenoic acid (EPA; 20:5n‐3) and docosahexaenoic acid (DHA; 22:6n‐3). Consequently, the seed production of marine fish requires careful nutritional enrichment of live feeds such as rotifers and brine shrimp Artemia to meet n‐3 HUFA requirements for normal growth. Another strategy for improving n‐3 HUFA availability is modifying the biosynthetic pathway of marine fish using transgenic technology. In this study, we conducted a feeding trial with non‐transgenic and transgenic nibe croaker Nibea mitsukurii carrying the elongation of very long‐chain fatty acids protein 2 (Elovl2) gene isolated from masu salmon Oncorhynchus masou and three groups of Artemia (non‐enriched and enriched with two products). For all Artemia groups, docosapentaenoic acid (DPA, 22:5n‐3), which is a direct product of Elovl2, was significantly higher in the transgenic fish than that in non‐transgenic fish, despite the absence of DPA in all diets. Thus, applying transgenic techniques to marine fish at the larval stage are a powerful strategy for modifying n‐3 HUFA biosynthetic pathways.